2019
DOI: 10.1007/s41669-019-0172-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Clinical Pharmacist Intervention on Medicine Costs in Patients with Chronic Obstructive Pulmonary Disease in India

Abstract: Background Chronic obstructive pulmonary disease (COPD) is a major cause of morbidity and mortality, especially in lowand middle-income countries (LMICs) such as India. Medicine costs are a key issue in LMICs, with typically high patient co-payments. In addition, pharmacists are underutilised in LMICs, including India. However, pharmacist-led educational interventions may improve the care of patients with COPD, as well as reduce medicine costs. Consequently, the objective of this study was to assess the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 74 publications
0
31
0
Order By: Relevance
“…Pharmacists and similar healthcare professionals in Bangladesh can prevent and manage patients with COVID-19 as well as help address unintended consequences 121,122 . This includes addressing issues of availability, access, and adherence to medicines in patients with chronic NCDs during the pandemic [123][124][125][126][127][128][129] . Potential activities also include giving guidance on prevention and possible treatments of COVID-19 based on evidence rather than misinformation as well as reinforcing Government messages to prevent the spread of COVID-19, including purchasing personal protection equipment (PPE) 122,[130][131][132][133] .…”
Section: Role Of Pharmacists and Others In Drug Stores In The Preventmentioning
confidence: 99%
“…Pharmacists and similar healthcare professionals in Bangladesh can prevent and manage patients with COVID-19 as well as help address unintended consequences 121,122 . This includes addressing issues of availability, access, and adherence to medicines in patients with chronic NCDs during the pandemic [123][124][125][126][127][128][129] . Potential activities also include giving guidance on prevention and possible treatments of COVID-19 based on evidence rather than misinformation as well as reinforcing Government messages to prevent the spread of COVID-19, including purchasing personal protection equipment (PPE) 122,[130][131][132][133] .…”
Section: Role Of Pharmacists and Others In Drug Stores In The Preventmentioning
confidence: 99%
“…In view of the contribution of the costs of medicines to total healthcare costs in India, coupled with existing high co-payments for visiting physicians and funding medicines, community pharmacies have and will continue to play an appreciable role in managing patients in India ( Abdulsalim et al, 2018 ; Daftary et al, 2019 ; Nafade et al, 2019 ; Abdulsalim et al, 2020 ; Sousa Pinto et al, 2020 ). Key reasons include avoiding paying physician fees, especially for milder symptoms, accessibility with long opening hours, and a lack of queues compared with ambulatory care clinics ( Soumya et al, 2016 ; Mohathasim Billah and Venkatesan, 2017 ; Daftary et al, 2019 ).…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…105,[107][108][109][110][111] In addition, the pharmacists as educators for COPD patients could also reduce medical costs, smoking behavior, and the frequency of lung deterioration. [112][113][114] These clinical practices demonstrated that the pharmaceutical care had shown favourable impacts on addressing drug-related problems such as medication adherence, hospital admission and medical costs, thus supporting its vital role in the management of COPD, especially when there is a wide range of therapeutic agents.…”
Section: Impact Of Pharmacist-led Medication Managementmentioning
confidence: 91%